2007
DOI: 10.1002/jhm.167
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children with neurological impairment who receive a fundoplication for gastroesophageal reflux disease

Abstract: BACKGROUNDChildren with neurological impairment (NI) commonly have gastroesophageal reflux disease (GERD) treated with a fundoplication. The impact of this procedure on quality of life is poorly understood.OBJECTIVESTo examine the quality of life of children with NI who have received a fundoplication for GERD and of their caregivers.METHODSThe study was a prospective cohort study of children with NI and GERD who underwent a fundoplication at a children's hospital between January 1, 2005, and July 7, 2006. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 44 publications
5
36
0
Order By: Relevance
“…It is known that for dystrophic and neurologically impaired children and their parents, lower preoperative functional and QoL scores throughout all dimensions [25] may correspond with a poorer functional outcome [2,4] and a higher recurrence rate [19] than for normal children [18]. On the other hand, it is suggested that otherwise healthy GERD patients benefit less from the operation and can therefore be managed medically [2].…”
Section: Discussionmentioning
confidence: 97%
“…It is known that for dystrophic and neurologically impaired children and their parents, lower preoperative functional and QoL scores throughout all dimensions [25] may correspond with a poorer functional outcome [2,4] and a higher recurrence rate [19] than for normal children [18]. On the other hand, it is suggested that otherwise healthy GERD patients benefit less from the operation and can therefore be managed medically [2].…”
Section: Discussionmentioning
confidence: 97%
“…We enrolled patients meeting the following criteria: (1) date of birth between January 1, 1997, and December 31, 2005; (2) having a previously published International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code for neurologic impairment, 12,20 with the following additions, demyelinating central ner (internal charge code) placed between January 1, 1997, and December 31, 2005, at PCMC (see Fig 1). GJTs were image-guided feeding tube placements after a previously placed gastrostomy feeding tube.…”
Section: Patientsmentioning
confidence: 99%
“…Chronic conditions were sorted hierarchically into mutually exclusive condition categories. At the top of the hierarchy was neurologic impairment (NI), defined as diagnoses consistent with static or progressive neurologic, genetic, or other diseases that typically result in functional and/or intellectual impairment, 16 followed by the following chronic conditions: congenital heart disease (CHD), cystic fibrosis (CF), systemic lupus erythematosus (SLE), sickle cell disease (SCD), inflammatory bowel disease (IBD), type 1 diabetes mellitus (DM), and asthma. Last, we explored 3 chronic mental health conditions: eating disorders, schizophrenia and related psychotic disorders (SZ), and mood and affective disorders (MA).…”
Section: Study Populationmentioning
confidence: 99%